Improved estimates for the effective elastic bulk modulus of random tetragonal crystal aggregates - Hanh, Vuong Thi My; Chinh, Pham Duc; Dong, Vu Lam (Vietnam Journal of Mechanics, 2016)
Particular expressions of upper and lower estimates for the macroscopic elastic bulk modulus of random cell tetragonal polycrystalline materials are derived and computed for a number of practical crystals. The cell-shape-unspecified bounds, based on minimum energy principles and generalized polarization trial fields, appear close to the simple bounds for specific spherical cell polycrystals.